AZD5363 Inhibits Inflammatory Synergy between Interleukin-17 and Insulin/Insulin-Like Growth Factor 1 - Chen, Chong; Zhang, Qiuyang; Liu, Sen; Lambrechts, Mark; Qu, Yine; You, Zongbing (Frontiers in Oncology, 2014)
In the United States, one third of population is affected by obesity and almost 29 million people are suffering from type 2 diabetes. Obese people have elevated serum levels of insulin, insulin-like growth factor 1 (IGF1) and interleukin-17 (IL-17). Insulin and IGF1 are known to enhance IL-17-induced expression of inflammatory cytokines and chemokines, which may contribute to the chronic inflammatory status observed in obese people. We have previously demonstrated that insulin/IGF1 signaling pathway crosstalks with IL-17-activated nuclear factor-kappa B (NF-κB) pathway through inhibiting glycogen synthase kinase 3β (GSK3β) activity. However, it is unclear whether GSK3α also plays a role and whether this crosstalk can be manipulated by AZD5363, a novel pan-Akt inhibitor that has been shown to increase GSK3 activity through reducing phosphorylation of GSK3α and GSK3β. In this study, we investigated IL-17-induced expression of C-X-C motif ligand 1 (Cxcl1), C-C motif ligand 20 (Ccl20) and interleukin-6 (Il-6) in wild-type, GSK3α-/-, and GSK3β-/- mouse embryonic fibroblast (MEF) cells as well as in mouse prostate tissues by real-time quantitative PCR. We examined the proteins involved in the signaling pathways by Western blot analysis. We found that insulin and IGF1 enhanced IL-17- induced expression of Cxcl1, Ccl20 and Il-6, which was associated with increased phosphorylation of GSK3α and GSK3β in the presence of insulin and IGF1. AZD5363 inhibited the synergy between IL-17 and insulin/IGF1 through reducing phosphorylation of GSK3α and GSK3β by inhibiting Akt function. These findings imply that the cooperative crosstalk of IL-17 and insulin/IGF1 in initiating inflammatory responses may be alleviated by AZD5363.